Sense of Quality dalam Pembelajaran Praktikum Teknik Pemesinan: Studi Kasus di SMK Mikael Surakarta - Valiant Lukad Perdana Sutrisno; Muhammad Nurtanto; Azaz Ramang Pambudi (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study examines how a sense of quality is formed in machining practicum learning from the perspective of teachers. The study contributes to the discussion on quality development in vocational education by exploring how attitudes, knowledge, and skills are integrated within practical learning environments. Methods – A qualitative case study was conducted in a vocational high school specializing in machining. Data was collected through semi-structured, in-depth interviews with four experienced teachers. The data were analyzed using iterative thematic analysis, including open coding, focused coding, and category development. Findings – The findings suggest that a sense of quality is developed through three interconnected dimensions. First, attitudes form the foundation, including responsibility, honesty, discipline, and resilience shaped through work experiences. Second, knowledge provides the conceptual and procedural framework, including understanding of standards, technical parameters, and production context. Third, skills represent the enactment of quality through planning, measurement, standard-based execution, reflection, and problem-solving. These dimensions are closely interrelated and indicate a pattern of quality development rather than a fixed system.Research Implications – The study offers an interpretative framework for understanding how quality awareness is constructed in vocational practicum learning.